Combination of KRAS and SMAD4 mutations in formalin‐fixed paraffin‐embedded tissues as a biomarker for pancreatic cancer. Issue 6 (30th May 2020) - Yokose, Takahiro; Kitago, Minoru; Matsuda, Sachiko; Sasaki, Yasushi; Masugi, Yohei; Nakamura, Yuki; Shinoda, Masahiro; Yagi, Hiroshi; Abe, Yuta; Oshima, Go; Hori, Shutaro; Yusuke, Fujita; et al.
Abstract: Formalin‐fixed paraffin‐embedded (FFPE) tissues used for routine pathological diagnosis are valuable for cancer genomic analysis; however, the association between mutation status derived from these specimens and prognosis in pancreatic ductal adenocarcinoma (PDAC) remains unclear. We analyzed 50 cancer‐related gene mutations including driver genes in PDAC, using next‐generation sequencing (NGS) to clarify the association between gene mutations and prognosis. DNA was extracted from FFPE tissues obtained from 74 patients with untreated resectable PDAC who underwent surgery at our institution between 2013 and 2018. Fifty of the 74 patients with DNA extracts from FFPE samples suitable for NGS were analyzed. The prevalence of driver gene mutations was as follows: 84% for KRAS, 62% for TP53, 32% for SMAD4, and 18% for CDKN2A . There were no cases of single SMAD4 mutations; its rate of coincidence with KRAS or TP53 mutations was 30% and 2%, respectively. The combination of KRAS and SMAD4 mutations resulted in significantly shorter relapse‐free survival (RFS; median survival time [MST], 12.3 vs. 28.9 months, P  = .014) and overall survival (OS; MST, 22.3 months vs. not reached, P  = .048). On multivariate analysis, the combination of KRAS and SMAD4 mutations was an independent prognostic factor for RFS (hazard ratio [HR] 4.218; 95% confidence interval [CI], 1.77‐10.08; P  = .001) and OS (HR 6.730; 95% CI, 1.93‐23.43; P  = .003). The combination of KRAS and SMAD4 mutations in DNA obtained from FFPE tissues is an independent poor prognostic factor in PDAC. Abstract : Next‐generation sequencing (NGS) assay targeted 50 cancer‐related genes using DNA extracted from 74 formalin‐fixed paraffin‐embedded (FFPE) tissues of patients with pancreatic ductal adenocarcinoma; mutations were detected in 94% of the 50 (70%) analyzed cases. First, the detection of KRAS and SMAD4 mutations in the resected specimen implied an increase in tumor recurrence with a poor chance of survival. Second, DNA extracted from FFPE tissue was feasible for analysis by NGS to arrive at an accurate prognosis.